PRODUCTION OF 3,5-DIALKYLSALICYLIC ACID - KINISHI RYOICHI; IKE TETSUJI (1990)
PURPOSE:To readily obtain the subject compound under mild conditions in high conversion and high purity by heating a 2,4-dialkyl phenol and alkali metal hydroxide in a specific mixed solvent to carry out azeotropic dehydration and successively subjecting the resultant reaction product to Kolbe-Schmitt reaction with CO2. CONSTITUTION:2,4-Dialkyl phenol and alkali metal hydroxide such as NaOH are heated in a mixed solvent consisting of a hydrocarbon-based solvent such as benzene and glycoldialkyl-based ether such as ethylene glycol dimethyl ether in the mixed ratio of 0.1 to 10 and subjected to azeotropic dehydration. Water content is removed out of system to afford substantially anhydrous 2,4-dialkyl phenol alkali salt, which is successively subjected to Kolbe-Schmitt reaction in the abovementioned solvent under 1 to 20kg/cm pressure of CO2 at 80 to 200 deg.C for 1 to 5hr to provide the objective compound useful as a synthetic raw material for chemicals such as developer for pressure-sensitive recording paper, agricultural chemical and antioxidant, etc.